The Adult Immigrant Woman: Testimonio of Her Educational Pathways - Cindy Peña (Adult Education Research Conference, 2023)
The purpose of this qualitative study was to document the educational experiences of adult Mexican immigrants and their convivencia in an adult English as a second language (ESL) classroom.
Keywords: English as second language; Immigrant women; Chicana feminist perspective; Testimonios